2018
DOI: 10.1136/bcr-2018-225120
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral air embolism from a Central Venous Catheter: A timely reminder of the importance of rapid diagnosis

Abstract: Cerebral air embolism (CAE) is a rare, avoidable and potentially fatal iatrogenic complication. Here, we report a case of CAE associated with a central venous catheter in the internal jugular vein that resulted in neurological deficits and generalised epileptic seizures. A 64-year-old man admitted for fasciotomy for compartment syndrome developed CAE with left-sided neurological deficits. The suspected origin was retrograde air flow from the right internal jugular venous catheter. The air spontaneously resorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(8 reference statements)
0
4
0
1
Order By: Relevance
“…Considering the pitfall of the anaesthetic management in this case and the fact that air embolism is reported as a very rare but a well-known possible complication during central ve nous catheter insertion [1,2], we recommend general anaesthetic management using positive pressure mecha-nical ventilation with PEEP when inserting a Hickman/Broviac catheter as well as a central venous catheter in paediatric patients, in order to prevent unexpected deep breathing in a spontaneous respiration, and to maintain a continuous positive intrathoracic pressure during the entire procedure from a risk management point of view, even though suspected pulmonary air embolisation cases during Hickman catheter insertion in paediatric patients have not been reported and its maker was unaware of such cases.…”
Section: Letters To the Editormentioning
confidence: 88%
See 1 more Smart Citation
“…Considering the pitfall of the anaesthetic management in this case and the fact that air embolism is reported as a very rare but a well-known possible complication during central ve nous catheter insertion [1,2], we recommend general anaesthetic management using positive pressure mecha-nical ventilation with PEEP when inserting a Hickman/Broviac catheter as well as a central venous catheter in paediatric patients, in order to prevent unexpected deep breathing in a spontaneous respiration, and to maintain a continuous positive intrathoracic pressure during the entire procedure from a risk management point of view, even though suspected pulmonary air embolisation cases during Hickman catheter insertion in paediatric patients have not been reported and its maker was unaware of such cases.…”
Section: Letters To the Editormentioning
confidence: 88%
“…Dear Editor, Air embolism is a very rare but wellknown and potentially fatal complication of central venous catheter insertion [1,2]. We experienced a paediatric case of suspected pulmonary air embolisation during insertion of a Hickman catheter with a peel-off sheath system (Medicon Inc., Osaka, Japan).…”
Section: Letters To the Editormentioning
confidence: 99%
“…Although the specific incidence is not available in the literature, a review article on air embolism by Brull et al reported at least 700 instances of air embolism on a search from an FDA mandatory device reporting database from 2011 to 2016 [1]. Central venous access has been frequently reported as a source of cerebral venous air embolism [2,3,4]. The proposed mechanism is that once air gains access to the venous system; ascension against blood flow is possible given the low specific gravity relative to blood [5].…”
Section: Discussionmentioning
confidence: 99%
“…This leads to the potential to precipitate gas in the hepatic veins, among other sites, due to slow flow within this system 8 . An additional mechanism of introduction of gas into the venous system could be due to the insertion of a femoral central line 14,15 . Similar to vascular air embolisms, gas could be introduced through disruption in the integrity of the venous circulation that occurs during insertion of ventral venous catheters 14 .…”
Section: Discussionmentioning
confidence: 99%